Analysis of Directive Speech Acts and Teacher Mitigation Strategies in Managing the Classroom - Moh. Tito Ragil Dianang; R. Panji Hermoyo (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
Effective pedagogical communication requires a balance between delivering firm instructions and maintaining emotional relationships with students. This study aims to describe the forms of directive speech acts and mitigation strategies used by teachers in managing classroom interaction at SMP Negeri 1 Ngoro Jombang. This Research is motivated by the importance of teachers' pragmatic competence in minimizing potential Face Threatening Acts (FTA) when giving orders to adolescent students. The method used is descriptive qualitative. Data sources were obtained from the utterances of Indonesian, Mathematics, and Science teachers in grade VIII during the learning process. Data collection was carried out using the Listen-glze-free method, recording, and note-taking techniques. Data analysis examines Searle's speech act theory and Blum-Kulka's mitigation strategy through an interactive analysis model. The results showed that directive speech acts of commanding and requesting were the most dominant forms. However, teachers tended to soften these instructions using mitigation strategies. Two main mitigation patterns were found: (1) Internal modification using lexical politeness markers such as "please", "try", and interrogative modes; and (2) External modification through providing reasons (grounders) before instructions. Specific findings indicate the use of code-switching to Javanese and the particle "nggih" as a cultural strategy to build rapport. It is concluded that the application of appropriate mitigation strategies is effective in creating a conducive, humanistic classroom atmosphere and increasing student compliance without coercion.